«Integral journalism» as a school of politics - Rapone, Leonardo (International Gramsci Journal, 2025)
The theme will be carried out under two distinct profiles: Gramsci the journalist and Gramsci the theorist of journalism. After reviewing the distinct phases of Gramsci's journalistic activity from 1915 to 1926, we will focus on his conception of journalism and the function he attributed to journalism in view of the development of the forms of a "new intellectualism". The final part of the essay will focus on the concept of "integral journalism" formulated by Gramsci in the Prison Notebooks and will analyse the composition of Notebook 24, a special notebook expressly entitled Journalism.